The problem of incommensurability in the approach capabilities of Sen (Cultura Económica, 2019)
Economics is a practical science, oriented towards certain ends. In this article, Professor Ricardo Crespo, following Amartya Sen, considers and analyses the rationality that this science uses in the adequacy of means to ends and in the definition of the ends themselves. In this aspect of the discipline, technical or instrumental rationality is opposed to practical rationality. The underlying problem would be then, the incommensurability of the ends, namely, the absence of a measurement instrument that provides an appropriate criterion in the election.
Keywords: incommensurability; technical rationality; practical rationality; comparison